Smoking Susceptibility Among Never-Smokers: Data From the 2006–07 National Youth Smoking Survey - Yang, Wiworn Sae (Can J Public Health, 2011)
OBJECTIVES: The purpose of this study was to explore school and individual characteristics associated with smoking susceptibility among a nationally representative sample of Canadian youth who were never-smokers. METHODS: Using data from the 2006–07 Youth Smoking Survey, multi-level logistic regression modeling was used to examine if student-level and school-level characteristics were associated with smoking susceptibility among grade 9 to 12 never-smokers. RESULTS: In 2006, 88.2% of Canadian youth in grades 9 to 12 were considered never-smokers, of whom 28.2% (n=255,840) were considered to be susceptible to future smoking. Significant between-school random variation in smoking susceptibility was identified, although the school-level smoking rate was not significantly associated with the risk of an individual student being susceptible. At the student level, smoking susceptibility was associated with having a sibling who smokes, having 1 or 2 close friends who smoke, having ever used alcohol or marijuana, being female and being in grade 9. Parental smoking and exposure to smoking in a car or in the home were not significantly associated with smoking susceptibility. CONCLUSION: One way to prevent smoking onset among youth is to interfere with the development of susceptibility to smoking in non-smoking youth population. We found that over 1 in 4 Canadian youth who were never-smokers in 2006 were considered susceptible to smoking in the future. Ongoing tobacco control prevention initiatives are crucial for reducing the prevalence of smoking susceptibility among non-smoking Canadian youth.